Recurrent Ileal Variceal Bleeding as a Diagnostic and Therapeutic Challenge - Marek Cingel; Jakub Benko; Matej Samoš; Marián Mokáň (Case Reports in Gastrointestinal Medicine)
Introduction. Massive ileal variceal bleeding is a rare intricate condition that needs rapid management and treatment. The absence of randomized clinical trials in this field leads to a lack of evidence-based diagnostic and therapeutical approaches. We present a case report describing imaging, endoscopic, and surgical procedures leading to the diagnosis and resolution of severe ileal variceal bleeding. Case Report. We admitted a 63-year-old patient for recurrent anemia and ongoing bleeding from the gastrointestinal tract presenting as enterorrhagia. We were not able to elucidate the source by endoscopic, angiographic, or nuclear imaging methods. As a last resort, we carried out a surgical procedure with peroperative enteroscopy and subsequent resection of the affected part of the intestine. Conclusion. We present a patient with a case of ileal variceal bleeding, which required extensive diagnostic and therapeutic effort with a unique peroperative enteroscopic approach.